2020
DOI: 10.1142/s0129065720500069
|View full text |Cite
|
Sign up to set email alerts
|

A Three-Dimensional Microelectrode Array to Generate Virtual Electrodes for Epiretinal Prosthesis Based on a Modeling Study

Abstract: Despite many advances in the development of retinal prostheses, clinical reports show that current retinal prosthesis subjects can only perceive prosthetic vision with poor visual acuity. A possible approach for improving visual acuity is to produce virtual electrodes (VEs) through electric field modulation. Generating controllable and localized VEs is a crucial factor in effectively improving the perceptive resolution of the retinal prostheses. In this paper, we aimed to design a microelectrode array (MEA) th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 81 publications
1
15
0
Order By: Relevance
“…Previous retinal stimulation models have been developed using cell physiology data, but with highly idealized FEMs of the implant and surrounding tissue. These models report activation thresholds orders of magnitude lower than clinical research studies [ 14 ]–[ 16 ], [ 31 ], [ 32 ]. By implementing an existing biophysical model into an anatomically realistic FEM, we predict absolute RGC activation thresholds in an amplitude range similar to perceptual thresholds.…”
Section: Resultsmentioning
confidence: 99%
“…Previous retinal stimulation models have been developed using cell physiology data, but with highly idealized FEMs of the implant and surrounding tissue. These models report activation thresholds orders of magnitude lower than clinical research studies [ 14 ]–[ 16 ], [ 31 ], [ 32 ]. By implementing an existing biophysical model into an anatomically realistic FEM, we predict absolute RGC activation thresholds in an amplitude range similar to perceptual thresholds.…”
Section: Resultsmentioning
confidence: 99%
“…As shown in Fig. 1, the eyeball model contained several basic structures, including cornea, atria, lens, vitreous body (VB), retina, choroid, and sclera [22], [23]. I listed the parameters [23], [24], [25], [26], [27].…”
Section: A Electrical Conductivity Model Of the Eyeball And Extraocular Electrodesmentioning
confidence: 99%
“…The steerable electric fields controlled by current ratios without physical electrode movability were similar to the concept of virtual electrodes, which was firstly applied in cochlear implants [30] and utilized for retinal prostheses currently [22], [31], [32]. But unlike the traditional virtual electrodes achieved by direct superposition of the electric field intensity, the movable direction of the interferential electric fields induced by the superposition of various current with different frequencies and amplitudes was closer to electrode pairs with the less output current.…”
Section: B the Steerability Of Focal Region By Changing The Current Ratiosmentioning
confidence: 99%
See 1 more Smart Citation
“…In most cases, the outer ring electrode served as a local return to confine the activated RGC region of the center electrode [24,25]. Some studies also showed that a group of ring-shaped electrodes could be used to produce virtual electrodes to enhance visual acuity [26]. The electrode pair design in this work had multiple functions as shown in Fig.…”
Section: B Increased Main-counter Electrode Impedance With Smaller El...mentioning
confidence: 99%